A7.4 The specificity of anti-carbamylated protein antibodies for rheumatoid arthritis in a setting of early arthritis. (13th February 2015) - Shi, J; van Steenbergen, HW; van Nies, JAB; van der Helm-van Mil, AHM; Huizinga, TWJ; Toes, REM; Trouw, LA
Abstract : Background and objectives: Anti-carbamylated protein (anti-CarP) antibodies have been described in rheumatoid arthritis (RA) and arthralgia. In anti-CCP2 negative RA patients the presence of anti-CarP was associated with more severe joint destruction. Here we investigated the sensitivity and specificity of anti-CarP antibodies for RA in a setting of early arthritis. Materials and methods: Anti-carbamylated fetal calf serum (anti-Ca-FCS), anti-CCP2 antibodies and rheumatoid factor (RF) IgM were measured by ELISA using serum samples available from the Leiden Early Arthritis Clinic cohort (EAC). For the anti-CarP antibodies we used as a cut-off for positivity the mean + 2 times the standard deviation of healthy controls. Results: In total 2086 sera of Leiden EAC patients suffering from early arthritis were analysed for the presence of anti-Ca-FCS antibodies. Anti-CarP antibodies were present in 26% of the patients and in 2% of the controls. We observed that the sensitivity and specificity of anti-Ca-FCS in the EAC cohort for RA are 44% and 89%. As a reference the sensitivity and specificity of anti-CCP2 antibodies are 54% and 96% and for RF IgM are 59% and 91%. Analysing the early arthritis patients that did not fulfil the EULAR/ACR 2010 criteria for RA that were anti-CarP positive (n = 127) revealed that these patients were mainly diagnosed as undifferentiated arthritis (45%), reactive arthritis (9%), psoriatic arthritis (9%) or peripheral spondyloarthritis (8%). Conclusions: Anti-CarP antibodies are predominantly present in RA but can also be detected in other forms of arthritis. The prognostic relevance of anti-CarP antibodies in these latter patients will have to be determined.